Static Magnetic Field Induced Neural Stem/Progenitor Cell Early Differentiation and Promotes Maturation. (16th October 2019) - Ho, Shih-Yin; Chen, I-Chun; Chen, Yi-Jyun; Lee, Chien-Hsing; Fu, Chao-Ming; Liu, Fei-Chih; Liou, Horng-Huei
Abstract : The potential impacts of magnetic field exposures on brain development have raised public concern. In the present study, we aimed to investigate the biophysical effects of moderate-intensity (0.5 T, Tesla) static magnetic field (SMF) on mice neural progenitor cells (mNPCs). Our results showed that the SMF exposure increased the number of neurosphere formation and enhanced proliferative activity in mNPCs. In addition, our flow cytometry data demonstrated that the proportions of S phase and G2/M phase mNPCs were remarkably increased following 5 days of SMF exposure. Moreover, the level of a mitotic regulatory protein, cyclin B, was upregulated after SMF exposure. Furthermore, the mNPCs exposed to SMF exhibited a significant increase in Sox2 expression. When mNPCs were induced to differentiation, our immunofluorescence assay revealed that the percentage of neurons (Tuj-1-positive cells) but not astrocyte (s100 β -positive cells) was significantly higher and displayed morphological complexity in the SMF group. Finally, our electrophysiological results demonstrated the mNPC-derived neurons from the SMF group showing a significantly increased in input resistance, which indicated more functional maturation. Based on these findings, it appears reasonable to suggest that SMF exposure could affect normal neurogenesis and promote neural lineage differentiation as well as neuronal maturation.